IMPLEMENTASI PROGRAM PRAKTIK KERJA LAPANGAN DI REGULATOR JASA KEUANGAN - Yustriana, Yustriana; Sri Poernomo, Baby (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This research aims to analyze the implementation of the field work practice program at the Financial Services Regulator and its impact on student competency development. The author uses a qualitative method with a case study approach. Data was obtained through in-depth interviews, and relevant documentation. The research respondents consisted of the OJK street vendor recruitment team, students participating in street vendors, and experts in the field of human resources. Data analysis techniques use IFAS (Internal Factors Analysis Summary), EFAS (External Factors Analysis Summary), and SWOT (Strengths, Weaknesses, Opportunities, Threats). The results of the study show that the street vendor program in the financial services regulator has strengths, such as OJK has many employees who have mastered competencies that have been certified in various fields so that OJK employees can participate in providing competent guidance for interns. However, there are weaknesses found in the implementation of street vendors, namely long administrative procedures, lack of hard skills and lack of soft skills from interns.